3(f + 6) = -6f - 9
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Divide both sides by 3:
f+6=-2f-3. Add 2f to each side:
3f+6=-3. Subtract 6 from each side:
3f=-9. Divide through by 3: f=-3.
Plug f=-3 into original eqn: 3*3=18-9=9. Correct!
by Top Rated User (764k points)

Related questions

1 answer
1 answer
asked Jul 16, 2013 in Algebra 1 Answers by anonymous | 299 views
1 answer
asked Aug 12, 2013 in Algebra 1 Answers by banana! | 127 views
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,099 questions
90,236 answers
60,442 users